Development of Ethnoscience E-Module Integrating Sedekah Laut to Enhance Biodiversity Learning - Luthfiyah, Firya; Haryani, Sri; Susilaningsih, Endang; Umam, Qo’idul; Jonathan, Adrovvy (Unnes Science Education Journal, 2025)
This research aims to determine the characteristics of Google Sites learning media integrated with Islamic values on Static Electricity material and its impact on the improvement of religious characters and critical thinking skills. The research method used is R&D with the ADDIE type. The research results show that the Google Sites learning media integrated with Islamic values on Static Electricity material is very valid for use. The validation scores from media and material experts were 4.38 and 4.42, respectively, with very valid criteria. The results of the data analysis show the N-Gain test results for 1 religious characters indicator with a high criterion and 7 religious character indicators with a medium criterion. The results of the N-Gain test for critical thinking skills showed 3 indicators with high criteria and 2 indicators with medium criteria. The results of the t-test for religious characters and critical thinking skills show a significant difference between the pretest and posttest scores. Based on the research results, the Google Sites learning media integrated with Islamic values on Static Electricity material is valid, usable, and can enhance the religious characters and critical thinking skills of the students.